2019
DOI: 10.2147/oajsm.s180408
|View full text |Cite
|
Sign up to set email alerts
|

<p>Block periodization of endurance training – a systematic review and meta-analysis</p>

Abstract: BackgroundBlock periodization (BP) has been proposed as an alternative to traditional (TRAD) organization of the annual training plan for endurance athletes.ObjectiveTo our knowledge, this is the first meta-analysis to evaluate the effect BP of endurance training on endurance performance and factors determinative for endurance performance in trained- to well-trained athletes.MethodsThe PubMed, SPORTdiscus and Web of Science databases were searched from inception to August 2019. Studies were included if the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
0
18
2
Order By: Relevance
“…In the current study, no clear differences in performance or performance-related measures between the two periodization models were observed. These findings contrast the findings of a recent meta-analysis by Molmen et al (2019) , indicating a small benefit of using BP. However, the findings of the different studies included in that meta-analysis ranged from no performance-benefits of BP over TP ( Breil et al, 2010 ; Garcia-Pallares et al, 2010 ; McGawley et al, 2017 ), to moderate, positive effects on performance and performance-related measures (e.g., VO 2peak , W max , and W 4mmol ) in both trained, and highly trained athletes ( Breil et al, 2010 ; Ronnestad et al, 2012 , 2014 , 2016 ; Clark et al, 2014 ; Costa et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the current study, no clear differences in performance or performance-related measures between the two periodization models were observed. These findings contrast the findings of a recent meta-analysis by Molmen et al (2019) , indicating a small benefit of using BP. However, the findings of the different studies included in that meta-analysis ranged from no performance-benefits of BP over TP ( Breil et al, 2010 ; Garcia-Pallares et al, 2010 ; McGawley et al, 2017 ), to moderate, positive effects on performance and performance-related measures (e.g., VO 2peak , W max , and W 4mmol ) in both trained, and highly trained athletes ( Breil et al, 2010 ; Ronnestad et al, 2012 , 2014 , 2016 ; Clark et al, 2014 ; Costa et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the individual, relative change in training load compared to habitual training load differed greatly and could be a reason for the substantial and similar improvements seen. The summary by Molmen et al (2019) indicates that BP only has a small benefit over TP in athletes with the weighted mean VO 2peak of 60 ml·kg −1 ·min −1 ( Molmen et al, 2019 ). It could be argued that the large and diverging improvements found in our participants would mask potential differences between BP and TP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis (Mølmen et al, 2019 ) reported evidence for beneficial short-term effects of BP compared to TRAD regarding VO 2max and maximal power output development in trained athletes, highlighting that BP of HIT could serve as an adequate, alternative strategy with potentially higher training effects than TRAD. However, the long-term adaptations following BP of HIT is currently not well-understood and requires further examination.…”
Section: Discussionmentioning
confidence: 99%
“…Positive short-term effects of using BP of HIT to augment training responses have been shown (Breil et al, 2010 ; Støren et al, 2012 ; Wahl et al, 2013 ; Clark et al, 2014 ; Rønnestad et al, 2017 ), whereas a recent study of junior XC skiers reported no beneficial effects of BP over TRAD (McGawley et al, 2017 ). In addition, a meta-analysis concluded that BP of HIT is an adequate, alternative strategy with potentially higher training effects than TRAD for trained to well-trained athletes (Mølmen et al, 2019 ). However, all these studies have compared the different periodization models by matching the overall HIT volume, whereas in practice, athletes also use BP of HIT to increase the overall HIT stimuli (Solli et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%